Issues of non-response: greater «coverage» of the sample or consolidation of the comparability criteria in data collection? - Tsouparopoulou, Eva (The Greek Review of Social Research, 2023)
The issue of non-response is of great concern to social scientists as response rates decline rapidly. The increase of the number of call-backs is commonly used as a practice to address this issue. This study investigates the effectiveness of call-backs for all 36 participating countries in the European Social Survey (ESS) and for the eight rounds (2002-2016). Also, the application (or not) of harmonized methodological rules for minimum response rates and the number of call-backs so as to ensure the overtime and cross-national comparability of data is examined. The results confirm the magnitude of the problem of non-response in social sample surveys and the inability of the participating countries to apply the strict methodological standards.